2010
DOI: 10.1002/crat.200900614
|View full text |Cite
|
Sign up to set email alerts
|

Influence of substrate temperature on the properties of electron beam evaporated ZnSe films

Abstract: ZnSe films were deposited on glass substrates keeping the substrate temperatures, at room temperature (RT), 75, 150 and 250 °C. The films have exhibited cubic structure oriented along the (111) which are attributable to 2TA LO phonon and TO phonon respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The deviation of the lattice parameter values from the bulk value observed here clearly suggests that the grains in the films are under stress. This deviation can be attributed to the change in the nature, deposition conditions and concentration of the native imperfections [16].…”
Section: Crystal Structurementioning
confidence: 99%
“…The deviation of the lattice parameter values from the bulk value observed here clearly suggests that the grains in the films are under stress. This deviation can be attributed to the change in the nature, deposition conditions and concentration of the native imperfections [16].…”
Section: Crystal Structurementioning
confidence: 99%
“…precursor molar concentrations were found to be equal to 2.12 eV, 2.08 eV, 2.06 eV and 2.02 eV, respectively. It is observed that the optical band gap decreases as the molar concentration of sulfur and tin (S:Sn) in the precursor solution increases and this red shift in the band gap values may be due to the quantum size effect [18]. The reduced band gaps with increasing precursor molar concentration may also be caused by deviation out of the S:Sn = 1 stoichiometry, which induces lattice faults in the films [19].…”
Section: Resultsmentioning
confidence: 99%
“…At the lower substrate temperatures, deposited films will have smaller grain sizes with larger grain boundaries which are highly distorted and thus they have large number of defect states. Therefore the films deposited at higher substrate temperatures will have comparatively larger grain sizes which can cause decrease in the defect states and thereby leads to increase the conductivity of the films [20][21][22].…”
Section: Structural Analysismentioning
confidence: 99%